Design of 0.92 Ghz artificial magnetic conductor for metal object detection in RFID tag application with little sensitivity to incidence of angle - Abu, Maisarah; Hussin, Eryana Eiyda; Othman , A.R (2014)
In this paper, the new structure of Artificial Magnetic Conductor is presented. The AMC is designed to overcome the failure of detecting the RFID tag when placed near to the metal based object. It is too complicated to design an AMC at low frequency due to limitation of size and bandwidth. In this paper, the 0.92 GHz AMC is designed with different sizes and shapes of slots inserted into the square PEC patch. The size of single unit cell of this AMC is 45.5 mm x 45.5 mm. The AMC is designed in stacked layer to increase the bandwidth of single unit cell. The optimized AMC at 0.92 GHz frequency, had increase the performance of dipole antenna by return loss = -21.8 dB, gain = 3.0 4dB and directivity = 5.149.